Design And Building of A Temperature and Humidity Control System For an Oyster Mushroom Cultivation Room Based on Arduino Mega - Akhyar, Lalu Tohirul; Darmawan, Budi; Paniran, Paniran (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2024)
Mushrooms are a type of exotic vegetable commodity that has quite high economic value and has great potential for cultivation. Oyster mushrooms are a type of mushroom that is much loved by Indonesian people and are a food source that is popular with people and contains quite high nutrition. The factors that determine mushrooms to grow well are temperature, humidity, CO2 levels and light intensity. This research aims to increase the efficiency of oyster mushroom cultivation by utilizing Arduino Mega technology in the oyster mushroom cultivation room and using a DHT-11 temperature sensor as a temperature and humidity detector in the oyster mushroom cultivation room. cultivation room. The parameters used to test the quality of the DHT-11 sensor are accuracy and normality test. The DHT-11 temperature sensor data is processed on the Arduino Mega and then displayed via LCD in real time. The system test results obtained in this research show that the system can work to control well with temperature values between 26-29°C with humidity 70-90%. From the results of the system test, the mushrooms will grow well.